Death following consumption of MDAI and 5-EAPB. (June 2019) - Deville, Marine; Dubois, Nathalie; Cieckiewicz, Ewa; De Tullio, Pascal; Lemaire, Eric; Charlier, Corinne
Highlights: First death case involving 5-EAPB and a combination of MDAI and EAPB. NPS purity can be high. Potential combined effects of NPS can surprise an experienced drug addict. Identification of EAPB isomer is an analytical challenge. Abstract: 5-(2-ethylaminopropyl)benzofuran (5-EAPB) and 5, 6-methylenedioxy-2-aminoindane (MDAI) are two new psychoactive substances (NPS) exhibiting MDMA-like properties. In this paper, we report the case of a 28-years old man, known as drug addict, found dead at home, with two unidentified powders next to him. External examination by the forensic pathologist was unremarkable but no autopsy was performed. Powders, blood and urine (which were the only samples available) were submitted to general unknown screening by high pressure liquid chromatography with a diode array detector (HPLC-DAD) and ultra high pressure liquid chromatography with a time-of-flight detector (UPLC-TOF-MS), after liquid–liquid extraction for biological samples, or simple dilution for powders. Analysis revealed 68% of MDAI in one powder and 87% of 5-EAPB in the other one. Significant levels of the same substances were found in blood (MDAI: 2.09 mg/L and 5-EAPB: 6.45 mg/L). The cause of death was therefore attributed to the consumption of these NPS since screening for other drugs of abuse and for alcohol was negative (oxazepam was found in urine only). 5-methylaminopropylbenzofuran (5-MAPB) and 5-aminopropylbenzofuran (5-APB) were also found in blood (0.089 and 0.546 mg/L, respectively) and urine (1.00 and 4.88 mg/L, respectively). In addition to the inherent complexity of NPS identification by itself, another analytical difficulty in this case was the identification of the EAPB positional isomer. Our routine screening methods were not able to distinguish the positional isomer, but an additional classical gas chromatography technique was able to make the distinction. Anyway, in our case, this issue was simplified thanks to the availability of a relatively pure powder that was analyzed by nuclear magnetic resonance (NMR).